Quality of initial HIV care in Canada: extension of a composite programmatic assessment tool for HIV therapy. Issue 3 (6th July 2016) - Kesselring, S; Cescon, A; Colley, G; Osborne, C; Zhang, W; Raboud, JM; Hosein, SR; Burchell, AN; Cooper, C; Klein, MB; Loutfy, M; Machouf, N; et al.
Abstract : Objectives: To document the quality of initial HIV care in Canada using the Programmatic Compliance Score (PCS), to explore the association of the PCS with mortality, and to identify factors associated with higher quality of care. Methods: We analysed data from the Canadian Observational Cohort Collaboration (CANOC), a multisite Canadian cohort of HIV‐positive adults initiating combination antiretroviral therapy (ART) from 2000 to 2011. PCS indicators of noncompliance with HIV treatment guidelines include: fewer than three CD4 count tests in the first year of ART; fewer than three viral load tests in the first year of ART; no drug resistance testing before initiation; baseline CD4 count < 200 cells/mm 3 ; starting a nonrecommended ART regimen; and not achieving viral suppression within 6 months of initiation. Indicators are summed for a score from 0 to 6; higher scores indicate poorer care. Cox regression was used to assess the association between PCS and mortality and ordinal logistic regression was used to explore factors associated with higher quality of care. Results: Of the 7460 participants (18% female), the median score was 1.0 (Q1−Q3 1.0−2.0); 21% scored 0 and 8% scored ≥ 4. In multivariable analysis, compared with a score of 0, poorer PCS was associated with mortality for scores > 1 [score = 2: adjusted hazard ratio (AHR) 1.64; 95% confidence interval (CI) 1.13–2.36; score = 3: AHR 2.02; 95% CI 1.38–2.97; score ≥ 4: AHR 2.14; 95% CI 1.43–3.21], after adjustments for age, sex, province, ART start year, hepatitis C virus (HCV) coinfection, and baseline viral load. Women, individuals with HCV coinfection, younger people, and individuals starting ART earlier (2000−2003) had poorer scores. Conclusions: Our findings further validate the PCS as a predictor of all‐cause mortality. Disparities identified suggest that further efforts are needed to ensure that care is equitably accessible.